Leaving the neighborhood for the urban center: Young İzzetpaşa Çiftliği Residents in the neoliberal urban order - Katırcı, İnci. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2009., 2009)
This study examines how the impact of neoliberalism is experienced by young gecekondu residents in Istanbul under the conditions of the changing urban economy and the restructuring of the city in accordance with neoliberal urbanism. The research was based primarily on interviews with a group of young residents from İzzetpaşa Çiftliği neighborhood in the vicinity of the central business district of Şişli. The results of the study indicated that as the young gecekondu residents have to a large extent lost the channels through which their families could carve out a place in the city after the 1950s, they tried to negotiate their places in the neoliberal urban order through their relationship with different places in the city. The informants of this study who could integrate to the neoliberal urban economy from lower positions as low-wage workers in the service sector, tried to differentiate themselves from their neighborhood and from its unemployed young residents whom they viewed as losers in the neoliberal urban order. In order to secure better places in this order, they opted out from the public places in their neighborhood and gravitated to the urban center which has been reshaped under neoliberal urbanism. As they tried to negotiate their places in the neoliberal urban order by reorganizing their relationship with different urban places, they both manipulated the neoliberal consumerist ideal through their tactics of using consumption places as nonconsumers and they reinforced this ideal in their attempts to differentiate themselves from the young people totally excluded from the neoliberal economy.
Keywords: Neoliberalism -- Turkey.; Urban renewal -- Turkey -- Istanbul.; City planning -- Social aspects -- Turkey.